2023
DOI: 10.1002/lary.30699
|View full text |Cite
|
Sign up to set email alerts
|

Esketamine versus Sufentanil Applied Prior to Placement of Suspension Laryngoscope

Abstract: ObjectiveIn laryngeal microsurgery, the insertion of the suspension laryngoscope is a strong stimulus that may cause hemodynamic fluctuations and adverse cardiovascular events. The purpose of this study was to compare the effect of preemptive treatment with esketamine and sufentanil on maintaining hemodynamics and reducing the occurrence of adverse cardiovascular events during the insertion of suspension laryngoscope.MethodsIn this double‐blind randomized controlled trial, patients undergoing general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[ 14 , 15 ] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [ 15 22 ] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients. [ 23 , 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 , 15 ] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [ 15 22 ] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients. [ 23 , 24 ]…”
Section: Introductionmentioning
confidence: 99%